2020
DOI: 10.1111/nan.12672
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric alterations in the default mode network during the progression of Alzheimer’s disease: Selective vulnerability of the precuneus

Abstract: The precuneus (PreC) corresponds to the mesial portion of Brodmann Area (BA) 7 and is a hub of the default mode network (DMN) that also includes frontal (BA10), inferior temporal (BA20) and posterior cingulate (BA23) cortices, which are compromised during the early stages of AD. 1-4 PreC imaging studies show marked hypometabolism 5-10 and extensive amyloid ligand binding in both mild cognitive impairment (MCI), a prodromal AD stage and frank AD. 1,11,12 However, this DMN node displays a resilience to synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 112 publications
(267 reference statements)
0
8
0
Order By: Relevance
“…Features of specific cells during AD exhibit features indicative of cells that undergoes senescence. For example, telomeric alterations and hyperproliferation-mediated DNA damage in cellular senescence have been observed in AD as well [ 52 ]. Particularly, one study demonstrated the correlation between AD and DNA double strand breaks where the authors have observed an increased γ-H2A.X (Ser139) positive neurons and GFAP positive astrocytes in the hippocampus of human AD postmortem brains compared to non-AD brains [ 53 ].…”
Section: The Role Of Ceramide In Ad Cell Linesmentioning
confidence: 99%
“…Features of specific cells during AD exhibit features indicative of cells that undergoes senescence. For example, telomeric alterations and hyperproliferation-mediated DNA damage in cellular senescence have been observed in AD as well [ 52 ]. Particularly, one study demonstrated the correlation between AD and DNA double strand breaks where the authors have observed an increased γ-H2A.X (Ser139) positive neurons and GFAP positive astrocytes in the hippocampus of human AD postmortem brains compared to non-AD brains [ 53 ].…”
Section: The Role Of Ceramide In Ad Cell Linesmentioning
confidence: 99%
“…It has also been found that patients with Alzheimer's disease (AD) and in the prodromal stage of AD have decreased DMN functions and precuneus GM volume compared to controls. Using post-mortem brains, a telomere length analysis of each brain region comprising the DMN showed that the precuneus telomere length was shorter in AD and prodromal stage of AD than in controls, whereas there were no differences in the frontal, inferior temporal, posterior cingulate gyrus or visual cortex [24]. Furthermore, this telomere length reduction in the precuneus was also correlated with cognitive task performance.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been found that patients with Alzheimer’s disease (AD) and in the prodromal stage of AD have decreased DMN functions and precuneus GM volume compared to controls ( Goto et al, 2015 ). Using postmortem brains, a telomere length analysis of each brain region comprising the DMN showed that the precuneus telomere length was shorter in AD and the prodromal stage of AD than in controls, whereas there were no differences in the frontal, inferior temporal, posterior cingulate gyrus or visual cortex ( Mahady et al, 2020 ). Furthermore, this telomere length reduction in the precuneus also correlated with cognitive task performance.…”
Section: Discussionmentioning
confidence: 99%